Searching for meaning in a post-scarcity society. Implications for creativity and job design - Pelligra, Vittorio; Sacco, Pier Luigi (Frontiers in Psychology, 2023)
The significance of meaningful and productive work, and the search for profound meaning within it, is akin to the air we breathe. Its importance is often realized only when it becomes contaminated or depleted. In contemporary societies, there is a growing awareness of the significance of the meaning of work, while simultaneously witnessing mounting mistrust and disillusionment as to the significance and social value of numerous jobs. There is paradoxically an increasing demand for meaningful work, while the supply of such work appears to be gradually decreasing. At present, we are recognizing the importance of this vital component that sustains our well-being as it begins to dwindle. The absence of meaningful work may stem from the nature of the work itself, the organizational environment in which it takes place, the prevailing corporate culture, or even the way in which tasks are defined and managed, which makes it challenging to find a sense of purpose and meaning in what we do. While progress can be made on both fronts, addressing cultural and organizational aspects is a more expedient means of intervention without the need of waiting for structural changes in the global economic and social systems.